A single left renal vein draining into the common iliac vein - Awad Bakhit Kaabneh; Sizeph Edward Haddad; Feras Ahmad Hammouri; Abdalla Yosef Omari; Mohammad K Abdadayem (Indian Journal of Urology, 2017)
Several variations of the anatomy of the left renal vein have been reported. Rare variants are frequently overlooked in the preoperative assessment but can lead to complications during surgery. We describe a kidney donor with a rare anomaly of a single main left renal vein draining into the left common iliac vein.